Recommended best management practices for Pueblo goldenweed (Oönopsis puebloensis: practices to reduce the impacts of road maintenance activities to plants of concern - Panjabi, Susan, author; Smith, Gabrielle, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2017)
Pueblo goldenweed (Oönopsis puebloensis) is a yellow flowered plant in the Asteraceae (Sunflower Family) that is known only from the Arkansas Valley in Pueblo and Fremont counties, Colorado, and is considered to be imperiled at a global and state level (G2/S2; Colorado Natural Heritage Program 2017). One of the biggest conservation issues for this imperiled plant species is the lack of awareness of its existence and status. Avoiding or minimizing impacts to this species during road maintenance activities will effectively help to conserve its habitat and is unlikely to confer substantial impacts on road maintenance goals and projects. The Best Management Practices (BMPs) included in this document are intended to help increase the awareness of this species for anyone involved in road maintenance activities.
Prepared for: the Colorado Natural Areas Program.
June 2017.
Keywords: Pueblo goldenweed; road maintenance impact; special management areas; noxious weed management; roadside plants